Optical absorption edge and luminescence in phosphorous-implanted Cu₆PS₅X (X = I, Br) single crystals - Studenyak, I.P.; Izai, V.Yu.; Stephanovich, V.О.; Panko, V.V.; Kúš, P.; Plecenik, A.; Zahoran, M.; Greguš, J.; Roch, T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Implantation of Cu₆PS₅X (X = I, Br) single crystals was carried out for
different values of fluence with using P+
ions; the energy of ions was 150 keV. For the
implanted Cu₆PS₅X crystals, the structural studies were performed using the scanning
electron microscopy technique and energy-dispersive X-ray spectroscopy. Spectrometric
studies of optical absorption edge and luminescence were carried out within the
temperature range 77…320 K. The influence of ionic implantation on luminescence
spectra, parameters of Urbach absorption edge, parameters of exciton-phonon interaction
as well as ordering-disordering processes in Cu₆PS₅X (X = I, Br) superionic conductors
have been studied.